Online biology journal Ritm ProBiologic – a teaching/learning strategy in the biology discipline - Coropceanu, Eduard; Placinta, Daniela (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2022)
The learning process in Biology requires adaptations to various conditions for achieving the didactic approach. Thus, the teacher undertakes the best strategies in maintaining the motivational character towards the Biology discipline. The online Biology journal Ritm ProBiologic (ProBiologic Rhythm) is a local product that promotes the values of education through thematic pages that address the multilateral aspects of biological sciences while promoting the principles of transdisciplinary learning as an element of modern teaching.